Development of Modern Physics Achievement Test: Validity and Reliability Study - Nuri Balta; Ali Eryılmaz (Foxton Books, 2020)
In this study, we aimed to develop an instrument that could be used to measure students' achievement in modern physics at high school level in a valid and reliable manner. The study was carried out in fall 2013-2014 with a total of 304 students. In this study, expert opinions were obtained to determine the test's content validity. The reliability of the test was obtained via Cronbach's alpha, which produced reliability coefficients that fell within acceptable limits. Item analysis were conducted to eliminate improper items. Based on these findings, it could be concluded that the test is an instrument that produces valid and reliable measures, and that can be used to determine students' achievement in modern physics.